A survey on the infection control techniques employed by selected dental laboratories in Metro Manila - Abundo, Florence S.; Gotay, Tanya N.; Sunico, Michelle (Adviser).
The American Dental Association (ADA), Center for Disease Control and Prevention (CDC) and the Occupational Safety and Health Administration (OSHA) have advocated the use of infection control procedures of dental laboratories. Some of these procedures include proper disinfection of incoming and outgoing cases, disinfection of working areas, use of barrier techniques, vaccination of employees against Hepatitis B and proper waste disposal. This study aimed to describe the compliance of the dental laboratories in Metro Manila with these procedures. A survey was done among 5 0 randomly selected dental laboratories in Metro Manila. Results showed that incoming and outgoing cases were not disinfected by the dental laboratories. The data also revealed that 34% properly disinfect working areas, the most commonly used protective barriers are masks (94%) and eyewear (54%) . About 36% of the samples claimed to 'have acquired vaccinations for Hepatitis B and at least 22% do proper waste disposal. The findings tend to show that compliance of these dental laboratories with the procedures and guidelines is poor.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Infection control, Dental